Azole-containing cationic bis-cyclometallated iridium(iii) isocyanide complexes: a theoretical insight into the emission energy and emission efficiency. Issue 26 (12th April 2019) - Giussani, Angelo; Pla, Paula; Junquera-Hernández, José M.; Ortí, Enrique
Abstract : Blue-emission of Ir(iii ) isocyanide complexes was quenched by a metal-centred d–d* triplet state. Abstract : Using a density functional theory approach, we explore the emission properties of a family of bis-cyclometallated cationic iridium(iii ) complexes of general formula [Ir(C^N)2 (CN- tert -Bu)2 ] + that have tert -butyl isocyanides as neutral auxiliary ligands. Taking the [Ir(ppy)2 (CN- tert -Bu)2 ] + complex (Hppy = 2-phenylpyridine) as a reference, the effect of replacing the pyridine ring in the cyclometallating ppy ligand by a five-membered azole ring has been examined. To this end, two series of complexes differing by the nature of the atom (either nitrogen or carbon) linking the azole to the phenyl ring of the cyclometallating ligand have been designed. Each series is composed of three molecules having an increasing number of nitrogen atoms (2 to 4) in the azole ring. The emission energies computed for the azole-containing [Ir(C^N)2 (CN- tert -Bu)2 ] + complexes show a generalized blue-shift compared to [Ir(ppy)2 (CN- tert -Bu)2 ] +, in agreement with the experimental data available for two of the six complexes designed here. The electronic nature of the lowest-lying triplet (T1 ) is clearly established as a ligand-centred ( 3 LC) state associated with the cyclometallating ligands, and cannot be described as a simple HOMO → LUMO promotion. Therefore, no clear trend based on the sole use of molecular orbital energies can be inferred to predict the emission properties. The significant oscillation in the emission quantum yield (ranging from 0.1% to 52%) experimentally reported is rationalized by the energy gap between the emitting T1 state and a non-radiative triplet state having metal-centred ( 3 MC) d–d* nature. On the basis of such a model, two of the here proposed systems are expected to display significant emission quantum yields in the blue region of the visible spectra, which make them good candidates for electroluminescent applications.